Strategi Komunikasi Persuasif Melalui Program Tebar Huffadz - Taufikkurrohman, Diki; Ahmad Habibul Muiz; Reka Gunawan; Luluk Fikri Zuhriah (Jurnal Dakwah dan Komunikasi, 2025)
The Tebar Huffadz program is a mosque-based initiative aimed at disseminating Qur'anic education within the community. This study seeks to analyze the persuasive communication strategies employed in the Tebar Huffadz program at Masjid Ibadurrahman Cembor, as well as to assess their effectiveness in enhancing community engagement and addressing existing social barriers. Adopting a qualitative approach with a case study design, this research focuses on the persuasive communication strategies implemented in the program. Data were collected through observations, in-depth interviews with the mosque’s management board (takmir), religious figures, and community members involved, as well as through program documentation. The findings reveal that the persuasive communication strategies used in this program include a personal approach to religious leaders, the use of familiar terminology within the community, and message delivery rooted in local and socio-religious values. These strategies have proven effective in introducing and implementing mosque-based programs in environments with strong religious affiliations. The utilization of community-recognized terminology, the involvement of religious leaders as primary communicators, and message delivery that prioritizes social and spiritual values are the key factors behind the program’s success